Kesulitan Belajar Tari Klana Raja Pada Mahasiswa Angkatan 2020 Prodi Pendidikan Tari Univeritas Lampung - Putri, Syafitri Kurnia (Jurnal Seni dan Pembelajaran, 2023)
This research aims to identify the factors contributing to learning difficulties experienced by students of the 2020 cohort in the subject of Klana Raja dance in the Dance Education Program at Lampung University. The research method employed is quantitative with a survey research design, aimed at illustrating issues based on facts and data obtained from the research results. The research participants include the lecturers teaching Javanese dance and students of the 2020 cohort in the Dance Education Program who have taken the course. Data collection was conducted through questionnaires and interviews. The questionnaire consisted of 51 statements referring to two indicators of learning difficulties, namely internal and external. The collected data was then analyzed using descriptive statistical analysis techniques, calculating the mean and percentage. The research findings indicate that the level of learning difficulties among students of the 2020 cohort in the Klana Raja dance subject in the Dance Education Program at Lampung University has a percentage of 66.03% and a mean value of 2.64. These findings suggest that learning difficulties are influenced by two main factors: intelligence factor, reaching a percentage of 83.49% with a very high category, and cultural background factor, reaching a percentage of 80.18% with a very high category.Keywords: Difficulties in Learning, students, Klana Raja dance